(untitled) (CIPEEX, 2026)
Fungal resistance represents a global therapeutic challenge, making the search for new antifungal agents urgent. Sapium haematospermum Müll. Arg. (milk stick), a species widely distributed in Brazil with reports of anti-inflammatory properties, emerges as a potential resource. This study aimed to investigate the in vitro antifungal activity of the ethanolic extract of S. haematospermum against Candida parapsilosis. The experimental research included the collection of botanical material, preparation of the ethanolic extract, and evaluation of its antimicrobial activity against ATCC standard strains. The techniques employed were plate sensitivity tests (Minimum Inhibitory Concentration - MIC), disk diffusion, and synergism with fluconazole. The results demonstrated that the extract, at different concentrations, did not inhibit the growth of C. parapsilosis alone. However, a promising synergistic effect was observed when the extract was associated with fluconazole, in addition to the formation of inhibition zones in the disk diffusion test. It is concluded that, although it does not have significant intrinsic antifungal activity, the extract of S. haematospermum presents compounds that potentiate the action of fluconazole, indicating a possible use as a resistance modulating agent.